“Honour”-based violence and the politics of culture in Canada: Advancing a cultural analysis of multiscalar violence - Abji, Salina; Korteweg, Anna (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2021)
Since 2015, in Canada, political discourse on “honour”-based violence has shifted away from highly problematic understandings of “culture” as the cause of violence among racialized, Muslim, and immigrant communities. Instead, talk of culture has dropped out of the equation altogether in favour of more structural definitions of gender-based violence (GBV). In this article, we ask what gets lost when culture is not taken into account when talking about or trying to understand forms of GBV. Drawing from theoretical conceptualizations of culture — defined as “situated practices of meaning-making” that shape all experiences of violence, and societal responses to violence — we argue for a multiscalar approach to culture. To illustrate this framework, we first offer a critical analysis of Aruna Papp’s 2012 memoir Unworthy Creature as an exemplar of stigmatizing uses of culture and a key text promoted by the Conservative federal government at the time. We then turn to interviews we conducted with service providers serving South Asian survivors of GBV in Toronto from 2011 to 2013. Our analysis illustrates how to talk about culture as a key ingredient shaping multiscalar violence, regardless of whether that violence occurs in majority or minority communities. We conclude with three policy implications for addressing HBV moving forward.